DISTRIBUTION AND PROTECTION OF POTENT TOXIC SUBSTANCES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article provides information on highly toxic substances, as well as an assessment of the chemical situation in case of accidents at chemically hazardous facilities, first aid to those poisoned and the procedure for protection against toxic substances.